Germline APC variants in patients with multiple colorectal adenomas, with evidence for the particular importance of E1317Q. - Lamlum, H; Al Tassan, N; Jaeger, E; Frayling, I; Sieber, O; Reza, F; Eckert, M; Rowan, A; Barclay, E; Atkin, W; Williams, C; Gilbert, J; et al. (2000)
Mendelian tumour syndromes are caused by rare mutations, which usually lead to protein inactivation. Few studies have determined whether or not the same genes harbour other, more common variants, which might have a lower penetrance and/or cause mild disease, perhaps indistinguishable from sporadic disease and accounting for a considerable proportion of the unexplained inherited risk of tumours in the general population. Germline variants at the APC locus are excellent candidates for explaining why some individuals are predisposed to colorectal adenomas, but do not have the florid phenotype of familial adenomatous polyposis. We have screened 164 unrelated patients with 'multiple' (3-100) colorectal adenomas for germline variants throughout the APC gene, including promoter mutations. In addition to three Ashkenazi patients with I1307K, we found seven patients with the E1317Q variant. E1317Q is significantly associated with multiple colorectal adenomas (OR = 11. 17, 95% CI = 2.30-54.3, p < 0.001), accounting for approximately 4% of all patients with multiple colorectal adenomas. In addition, four patients with truncating APC variants in exon 9 or in the 3' part of the gene were identified. Germline APC variants account for approximately 10% of patients with multiple adenomas. Unidentified predisposition genes almost certainly exist. We argue that it is worthwhile to screen multiple adenoma patients for a restricted number of germline APC variants, namely the missense changes E1317Q and I1307K (if of Ashkenazi descent), and, if there is a family history of colorectal tumours, for truncating mutations 5' to exon 5, in exon 9 and 3' to codon 1580.